2006
DOI: 10.1091/mbc.e06-01-0008
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte Chemotaxis Is Regulated by Histone Deacetylase 6, Independently of Its Deacetylase Activity

Abstract: In this work, the role of HDAC6, a type II histone deacetylase with tubulin deacetylase activity, in lymphocyte polarity, motility, and transmigration was explored. HDAC6 was localized at dynamic subcellular structures as leading lamellipodia and the uropod in migrating T-cells. However, HDAC6 activity did not appear to be involved in the polarity of migrating lymphocytes. Overexpression of HDAC6 in freshly isolated lymphocytes and T-cell lines increased the lymphocyte migration mediated by chemokines and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 55 publications
3
84
1
Order By: Relevance
“…HDAC6 overexpression promoted chemotactic movement of fibroblasts and lymphocytes, suggesting that HDAC6-mediated tubulin deacetylation regulates microtubule-dependent cell motility. 55,56 Nevertheless, there is contradictory data on the importance of HDAC6 in regulation of cellular motility (reviewed in ref. 57).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HDAC6 overexpression promoted chemotactic movement of fibroblasts and lymphocytes, suggesting that HDAC6-mediated tubulin deacetylation regulates microtubule-dependent cell motility. 55,56 Nevertheless, there is contradictory data on the importance of HDAC6 in regulation of cellular motility (reviewed in ref. 57).…”
Section: Discussionmentioning
confidence: 99%
“…57). It has therefore been proposed that HDAC6 expression per se but not its tubulin deacetylase activity is important for its effect on cell migration 56 and that these effects may be mediated by downstream factors like HSP90. 58 As high micromolar drug concentrations are impractical for clinical applications, we sought to find suitable combination regimens that would allow a dose reduction through synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Cabrero et al (2006) have recently found that the cellular levels of HDAC6 and not its catalytic activity are critical for lymphocyte chemotaxis.…”
Section: Deacetylase-dependent Functions Of Hdac6mentioning
confidence: 99%
“…Indeed, loss of HDAC6 causes a reduction in cell motility both in NIH/3T3 fibroblasts [4,5] and lymphocytes [24]. HDAC6 may thus be a cellular homeostasis surveillance factor.…”
Section: Hdac6 Regulates Mitochondrial Metabolic Activity In the Cytomentioning
confidence: 99%